2021
DOI: 10.18662/po/12.2/294
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Relationship Between Perfectionism and Feelings of Loneliness of Youths

Abstract: The purpose of the study is a theoretical substantiation and empirical study of the psychological content parameters of the relationship between perfectionism and feelings of loneliness in youth. A new view of modern reality with its constant changes and increased requirements for the functioning of the individual in society has been substantiated. It is noted that such a view provokes the mass formation and spread of perfectionism and loneliness. It is noted that every day more and more people, especially you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This fits with Hewitt and Flett (1990), who found that early life experiences (e.g., parental expectations and concern over mistakes) can lead to the manifestation of perfectionistic behaviours in children where they are driven to meet the real or perceived expectations that they believe others hold for them [23]. Due to their belief that their relationships are superficial, individuals may perceive their key relationships as being insecure [30] and thereby potentially instil a sense of loneliness [31,32]. Alternatively, those who are able to maintain a persona of perfection may develop superficial relationships, which leads to feelings of loneliness to arise as they do not assume social acceptance [33,34].…”
Section: Discussionsupporting
confidence: 57%
“…This fits with Hewitt and Flett (1990), who found that early life experiences (e.g., parental expectations and concern over mistakes) can lead to the manifestation of perfectionistic behaviours in children where they are driven to meet the real or perceived expectations that they believe others hold for them [23]. Due to their belief that their relationships are superficial, individuals may perceive their key relationships as being insecure [30] and thereby potentially instil a sense of loneliness [31,32]. Alternatively, those who are able to maintain a persona of perfection may develop superficial relationships, which leads to feelings of loneliness to arise as they do not assume social acceptance [33,34].…”
Section: Discussionsupporting
confidence: 57%